STRATEGI PENGEMBANGAN PESISIR PANTAI DESA LIANG SEBAGAI KAWASAN OBJEK PARIWISATA - Roy A Wattimena (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
Coastal development strategy of Liang Village as tourism object area hasnot been implemented properly, where the role of government is very dominantcompared to the community and the absence of an ideal concept resulted in manyproblems that arise. This study aims to determine the strategies implemented byLocal Government with the community in developing coastal village of Liang astourism object area. This research uses descriptive qualitative approach usingobservation process along with interview where the subject of research is Head ofTourism Product and Business Department of Tourism and Creative Economy ofMaluku Province, Head of Liang Village, Community of Traders at Liang VillageBeach. The research instrument is self-researcher and to test and check the validityof data used used source triangulation technique.The results of this study provide an illustration that the supporting factorsin the development of coastal Liang Village is to have the potential of touristattraction or tourism object in the form of coastal areas are quite wide and long,the public support for tourism development and the government's concern intourism development. Inhibiting factors are land ownership status which resultedin the development process of coastal areas is limited, public awareness is notgood about the tourism awareness and charm, the limited facilities andinfrastructure of tourism, and limited funds available in the development ofcoastal areas as the object of coastal tourism. Strategy that must be developed isformulation strategy by making scale development priority that is making productmarketing and implementation strategy by applying of management function thatis institutional strengthening.